THE EFFECT OF TRANSCUTANEOUS ELECTRICAL NERVE STIMULATION (TENS) TOWARDS WOUND HEALING - SATRIYA PRANATA (NURSCOPE: Jurnal Penelitian dan Pemikiran Ilmiah Keperawatan, 2016)
Background: Instead of reduce pain, TENS is also capable of stimulating the peripheral nerves to work optimally and improving blood circulation where the electrodes are applied. Having good blood circulation enhances good wound healing as well. The decrease in pain level will boost the immune system thus the wound healing can also be improved. It needs further studies on the effect of TENS on wound healing. Objective: The research aimed to explore specific effect of TENS on wound healing. Methodology: The research was conducted by using Science Direct article, Medline, Google Search and Pro Quest to find articles which are appropriate with inclusion and exclusion criteria to be reviewed. Results: The necrosis cases of the post-operative wound were higher in the control compared to the intervention group, there were no complications with significant p-value of (P <0.0001). There were differences in the provision of TEENS with additional of heat protocol before, during and after the intervention towards the blood circulation with the significance p value of (P, 0.05). Good granulation occurs, the hair follicle grew well and Pro-inflammatory declined (TNF-α) with the significance p-value of (P <0.05). The comparison of necrosis percentage in five groups were 43.88%, 39.20%, 38.57%, 32.14% and  44.13% in G1 to G5 respectively. The statistical tests proved the TEENS intervention in group G4 was more effective with the significance p value of  0.032. The TENS with frequency of 10 Hz is more effective compared to 100 Hz TENS and control groups who received placebo towards the adrenergic receptor. TENS intervention at a dose of 100 Hz can improve the reactivity of venous blood circulation well. The amount of oedema in the wound is reduced and capillary refills 2 seconds with the significance p-value of (P <0.001) significantly. Discussion: TENS at a frequency of 10 Hz to 100 Hz is the bioelectrical body frequency. At low frequencies, it will be able to stimulate the secretion of endorphin hormone so the patients who received TENS intervention can be more relaxed and feel better as the pain is relieved. The immune system works well and can help the wound heals properly by inhibition of inflammatory factor. Conclusions: TENS therapy is proven to help wound healing. TENS equipment is available everywhere, easy to use, economical, does not cause addiction, and can be given at any time with fewer side effects to the patients. The results of the study cannot be generalised yet. Further research is needed. Keywords: Transcutaneous Electrical Nerve Stimulation, wound healing, literature review.